Structural, Electronic, and Spectroscopic Insights Into Pralsetinib via Density Functional Theory and in Silico Toxicity Assessment - Kebiroglu, Mehmet Hanifi; Hssain, Ala; Allame, Sara Sabah Khaeoon; Kaygili, Omer; Bulut, And Niyazi (Wiley-V C H Verlag Gmbh, 2026)
This study investigates the structural, electronic, and toxicological properties of Pralsetinib using DFT at the PBEPBE/6-31G level. Topological analyses (NCI and ELF) confirmed stable non-planar geometry supported by weak interactions. FMO analysis revealed a narrow energy gap (Delta E = 2.126 eV), characterizing Pralsetinib as a chemically soft and reactive molecule, consistent with DOS and Fukui function calculations. Spectroscopic properties (FT-IR, NMR, UV-vis) were simulated to explain the molecular framework. In silico toxicity assessments (ProTox-3.0 and T.E.S.T.) predicted an LD50 of 800 mg/kg (GHS Class 4). While the molecule was non-mutagenic and non-carcinogenic, potential risks for neurotoxicity and respiratory toxicity were identified. These findings provide a comprehensive profile for future pharmacological evaluations.
Keywords: DFT; HOMO-LUMO; LD50; molecular docking; toxicity